PENGEMBANGAN MEDIAPEMBELAJARAN VIDEOTUTORIAL MATA PELAJARANSENI BUDAYAKELASVIII DI MTsN - Arrasy Mayrilla; Zuliarni Zuliarni (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
ABSTRACTThe development of learning video media using the Adobe Premiere application is an effort to help students understand the messages of learning in a practical and time-saving manner in learning process. This study aims to (1) develop learning media with tutorial video that can be applied tograde VIII in  MTsN ofSeniBudaya subject and (2) produce tutorial video learning media that is practice to be applied inMTsN ofSeniBudaya subject.The procedure developed in this development research refers to the simplified procedural model of Brog& Gall according to research needs. The results of analysis based on trials for the practicality of video media product are in the practical category used evenly overall score of 4.66. So based on the results of validity and practicality tests it can be concluded that this video media product is valid and practical and is suitable for use in learning.Keywords       : Video Tutorial, Seni Budaya, Bansi